Children of the river - Crew, Linda (New York Bantam Doubleday Dell Books for Young Readers, 2001)
Having fled Cambodia four years earlier to escape the Khmer Rouge army, seventeen-year-old Sundara is torn between remaining faithful to her own people and enjoying life in her Oregon high school as a "regular" American
Laurel-Leaf Books
Keywords: Asian Americans / Juvenile fiction; Khmers / Juvenile fiction